2021
DOI: 10.3390/cryst11030225
|View full text |Cite
|
Sign up to set email alerts
|

Neutron and XRD Single-Crystal Diffraction Study and Vibrational Properties of Whitlockite, the Natural Counterpart of Synthetic Tricalcium Phosphate

Abstract: A crystal chemical investigation of a natural specimen of whitlockite, ideally Ca9Mg(PO4)6[PO3(OH)], from Palermo Mine (USA), was achieved by means of a combination of electron microprobe analysis (EMPA) in WDS mode, single-crystal neutron diffraction probe (NDP) and single-crystal X-ray diffraction (XRD), and Fourier transform infrared (FTIR) spectroscopy. The crystal-chemical characterization resulted in the empirical formula (Ca8.682Na0.274Sr0.045)Σ9.000(Ca0.034□0.996)Σ1.000(Mg0.533Fe2+0.342Mn2+0.062Al0.046… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 50 publications
2
15
0
Order By: Relevance
“…In the HETCOR spectrum measured using 2 ms contact time the correlation from the impurity phase is masked, though the correlation between the P(2) phosphorus and HPO 4 proton is now better seen. According to the neutron diffraction data published very recently by Capitelli et al 4 for natural WH, the HP(1)O 4 tetrahedron may flip 180° along the c -axis. This results in the displacement of P(1) along the c axis and two different positions of protons – downward ( −c ) and upward ( +c ).…”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…In the HETCOR spectrum measured using 2 ms contact time the correlation from the impurity phase is masked, though the correlation between the P(2) phosphorus and HPO 4 proton is now better seen. According to the neutron diffraction data published very recently by Capitelli et al 4 for natural WH, the HP(1)O 4 tetrahedron may flip 180° along the c -axis. This results in the displacement of P(1) along the c axis and two different positions of protons – downward ( −c ) and upward ( +c ).…”
Section: Resultsmentioning
confidence: 96%
“…Besides being a biomineral existing in the human body, Mg-WH can also be found in nature. The first studies on the structural properties of natural and synthetic Mg-WH were performed by Gopal et al 2,3 in the early 1970s; however, just recently a neutron diffraction study of natural WH was reported by Capitelli et al 4 It is noteworthy that due to the hardly distinguishable X-ray diffraction patterns of β-TCP and Mg-WH, these two names are often used in the literature interchangeably and synonymously. Nevertheless, the crystal structures of β-TCP and Mg-WH differ significantly.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…β-TCP is rhombohedral with space group R3c (a = b = 10.4352(2) Å; c = 37.4029(5) Å; V = 3527.26 Å 3 [20]) and, at T > 1125 • C, changes into the polymorph phase α-TCP, monoclinic in P2 1 /a (a = 12.887(2) Å; b = 27.280(4); c = 15.219(2) Å; β = 126.20(1) • ; V = 4317.52 Å 3 [21]); the β → α transition in TCP may occur later at a higher temperature in the presence of RE 2 O 3 reactants [6], as in the case of the present RE-TCP samples calcined at 1200 • (see Synthesis paragraph) but displaying a β-TCP structure as described later. β-TCP has its natural counterpart in the isotypic mineral whitlockite, ideally Ca 9 Mg(PO 4 ) 6 [PO 3 (OH)], rhombohedral in R3c (a = b = 10.357(3) Å, c = 37.095 (15) Å and V = 3446(2) Å 3 ) [22]; because of isotypicity among natural whitlockite and β-TCP, the latter is often indicated as synthetic whitlockite, and its structure is indicated as whitlockite-type. TCP presents a third polymorph, the high-pressure form known as γ-TCP, rhombohedral in R-3m, usually coming from transformation both at high temperature and pressure of β-TCP [23]; it is also found with mineral name tuite in chondritic meteorites, as a result of shock impact of other calcium phosphate minerals [24].…”
Section: Discussionmentioning
confidence: 99%
“…In the isotypic mineral whitlockite, despite the presence of Mg 2+ replacing Ca 2+ at the M5 octahedral site, there are no substantial modifications in number and coordination of sites [22]. Eventually, M4 coordination number possibly increases up to six, due to a second group of three oxygen atoms related for symmetry found over 2.81 Å [22], providing very weak contributions in terms of valence bonds [33].…”
Section: Polyhedral Environmentmentioning
confidence: 99%